Analisis Penerapan Standard Operating Procedure (SOP) Pengadaan Barang dan Jasa pada Divisi Procurement PT Mandom Indonesia Tbk - Ana Yuliyana; Puji Wahono; Rizki Firdausi Rachmadania (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2025)
This study aims to analyze the implementation of Standard Operating Procedures (SOP) in the procurement of goods and services within the Procurement Division of PT Mandom Indonesia Tbk. SOP serves as a key guideline to ensure operational efficiency. Using a descriptive qualitative approach and case study method, data were collected through interviews, observations, and documentation with five informants involved in procurement activities. The results show that the SOP has been generally well applied and integrated with the e-Procurement system. However, several obstacles were identified, including unclear user requests, urgent demands, and limited vendor availability. These challenges are mainly caused by human resource constraints, lack of coordination, and system readiness issues. To address these problems, the informants suggested improving communication, conducting regular SOP socialization, adopting flexible procedures when needed, and evaluating vendor performance. The study concludes that effective SOP implementation requires not only clear procedures but also organizational readiness, communication, and adaptability to real conditions.